منهجية تدوين التاريخ ا س مي: قراءة نقدية (The Methodology of Writing Islamic History: A Critical Analysis) - Grine, Fadila; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2012)
Throughout many centuries of change and development, the Islamic history continues to represent the memory reservoir of the Muslim nation with its multiple backgrounds and affiliations. The need for a critical method of the Islamic history to help us captures its diversity and richness is unavoidable. This study adopts an approach of critical analysis to examine the reasons causing a declining historical objectivity alongside a sort of a poor vision affecting the process of historical writing and codification throughout longer period of time. This research discusses the different factors that negatively affected the writing of the Islamic history and draws on the sources of the revelation in its capturing of a number of historical events and developments of previous nations. This inquiry highlights the rational justifications for interpretation of the Islamic history and the need for an integrated approach to the Islamic history. Such an approach however, is required to merge issues of chains of transmission with the need for critiquing the historical texts in addition to the use of modern science to filter and scrutinize the historical transmitted historical materials found in the Islamic heritage. This exploration would be instrumental for current research on Islamic history, particularly on the process and style of re-writing past Islamic historical themes for contemporary contexts.